SEJARAH SOSIAL IMAM MALIK - Anwari, Amalia Nur; Hasanuddin, Maulana; Anwar, Syahrul (Jurnal Res Justitia: Jurnal Ilmu Hukum, 2025)
This research discusses how the social history of Imam Malik Imam Malik bin Anas (711-795 AD), is one of the most famous Islamic scholars in history. He also created the Maliki school, which is one of the four most important schools of Islamic fiqh. Imam Malik was born in Medina, a place rich in religious and intellectual traditions, which shaped his thinking. He is known for his unique method of ijtihad, which prioritizes the practices of the people of Medina as a source of law, and integrates hadith and the opinions of the Prophet's companions. His famous work, Al-Mudawwanah, is an important reference in the study of fiqh and shows his deep thoughts on justice and public interest (maṣlaḥah). Imam Malik also emphasized the importance of morals and morals in the application of law. He still influences the development of Islamic law and is a reference for many Muslims around the world. Imam Malik contributed greatly to the understanding and practice of Islamic law to this day by utilizing a balanced approach between text and context. This article aims to find out how the social history of Imam Malik's journey.